Youth perspectives on information and trust during COVID-19: evidence from Egypt - Seddik, Salma; Aboushady, Ahmed Taha; Nawwar, Ahmed; Emam, Omar; Hemida, Mahmoud; Zohny, Mennatallah; Ramadan, Adham; Aboismail, Eslam; Elsaid, Noha M. AbuBakr; Hegazy, Amira (Frontiers in Digital Health, 2025)
IntroductionThe detrimental effects of the COVID-19 global pandemic have significantly changed the world's view on enacting policies. Egypt has adopted various protocols and measures to control the spread of its causative virus, SARS-CoV-2. This study aims to examine the public trust in decision-makers and help address possible gaps between the sources of information, theoretical guidelines, implementation, and the confidence of youth in response to the pandemic by the main actors involved.MethodsAn online structured cross-sectional survey was conducted among Egyptian youth during the early COVID-19 pandemic. The questionnaire collected variables, including socio-demographic characteristics, sources of information, and the respondent's confidence in these sources.ResultsOut of 406 online respondents, males and females represented, 41.8% and 58.6%, respectively. Ninety-five percent of the respondents received a university or postgraduate education, of which 63.5% were in the medical field, and 82.3% lived in rural areas. Over forty percent reported their source of information was T.V., and 30.3% relied on social media, despite most of the respondents being unconfident in both. In addition, 12.8% and 5.9% reported that their source of information was the Ministry of Health and the WHO, respectively. Over seventy-seven percent of the respondents were concerned with the decisions taken by key actors in the pandemic situation, while 15% were neutral, and 5.4% were not concerned.ConclusionInfodemics is a substantial public health threat. Public health authorities and governments should take action to ensure comprehensive health information literacy and develop information technology strategies that promote access to evidence-based information.